Outcomes of Surgical Treatment for Displaced Both-Column Acetabular Fractures - Nikola Bulatović; Nadomir Gusić; Tomislav Čengić (Acta Clinica Croatica, 2023)
Complex both-column acetabulum fractures are severe injuries, often with associated injuries and complications with uncertain clinical and functional outcome. Modern traumatological protocols point to early surgical treatment, with anatomical reduction and stable internal fixation of fragments as a prerequisite for achieving a good treatment outcome. This retrospective-prospective multicenter cohort study was conducted during the 2014-2020 period and included 24 cases that met the input parameters, using the Letournel and Judet classification, and application of a combined surgical approach, a modified Stoppa and Kocher-Langenbeck approach. The results of treatment with complications, associated injuries and functional outcome are described. Fractures were caused by high kinetic energy trauma, and the cause was traffic accident in 17/24 (70.84%), fall from a height in 5/24 (20.83%) and crash injuries in 2/24 (8.33%) cases. The sample included 18 (75.00%) male and 6 (25.00%) female, with 10/24 (41.67%) right sided and 14/24 (58.33%) left sided fractures. Their mean age was 45.06 (range, 24-62) years. The mean follow-up time was 2.8 (range, 1-5) years. Postoperative complications were detected in 14/24 (58.33%) cases, including wound infection in 4/24 (16.67%), deep vein thrombosis in 2/24 (8.33%), heterotopic ossification in 2/24 (8.33%), hip osteoarthrosis in 3/24 (12.50%), avascular necrosis of femoral head in 2/24 (8.33%), total hip arthroplasty procedures in 3/24 (12.50%), abdominal complications in 2/24 (8.33%), urologic complications in 2/24 (8.33%), iatrogenic nerve lesion in 3/24 (12.50%), and fatal pulmonary embolism in 2/24 (8.33%) cases; there was no loss of reduction or non-union acetabular fracture. Associated injuries that we recorded as major trauma were presented in 13/24 (54.17%) study patients. The final functional results according to the Harris Hip Score (HHS) were excellent in 7/22 (31.82%), good in 10/22 (45.45%), moderate in 4/22 (18.18%) patients, and poor in 1/22 (4.55%) patient. The mean HHS was 84 (range 34-98). Complications and results have led us to a conclusion that primary injuries significantly affect the clinical and functional results. A good diagnostic procedure, assessment of the general condition and application of the trauma scoring system, surgical treatment that includes early hip reduction, open reduction internal fixation and physical rehabilitation are necessary.